A Review of Predictive Factors of Student Satisfaction with Online Distance Learning: A Systematic Literature Review - Chen, Mengying; Mohammed , Lubna Ali (Journal of Ecohumanism, 2024)
From 2020 to 2023, university students worldwide experienced online distance learning (ODL), during this unique period, the satisfaction of students received extensive research attention. This study conducts a systematic literature review, selecting 68 relevant articles on ODL satisfaction factors from the Web of Science, Science Direct, and ProQuest databases. The study aims to explore research trends, influencing factors, and future agendas related to ODL satisfaction. The findings reveal that: 1). Recent research primarily focuses on Asian countries and developing nations. The most commonly used research method is quantitative, combining surveys with Structural Equation Modeling (SEM). University undergraduates are the most frequent subjects of these studies. 2). In examining influencing factors, it is found that ODL satisfaction research mainly includes five aspects: student factors, teacher factors, course factors, information technology and tools, and macro-environmental factors. Key influencing factors are concentrated on "interaction," "self-efficacy," "engagement," "motivation," "teacher quality," "course content quality," "course assessment," "information technology," and "learning management systems." These terms represent the most frequently studied factors in recent satisfaction research. 3). For future research on ODL satisfaction, researchers can further expand their studies from theoretical, technological, and practical application perspectives.